Acyl CoA Binding Proteins are Required for Cuticle Formation and Plant Responses to Microbes - Xia, Ye; Yu, Keshun; Gao, Qing-ming; Wilson, Ella; Navarre, Duroy; Kachroo, Pradeep; Kachroo, Aardra (Frontiers in Plant Science, 2012)
Fatty acids (FA) and lipids are well known regulators of plant defense. Our previous studies have shown that components of prokaryotic (plastidal) FA biosynthesis pathway regulate various aspects of plant defense. Here, we investigated the defense related roles of the soluble acyl CoA binding proteins (ACBP), which are thought to facilitate the intracellular transport of FA/lipids. We show that ACBP3 and 4 are required for maintaining normal lipids levels and that ACBP3 contributes to the lipid flux between the prokaryotic and eukaryotic pathways. We also show that loss of ACBP 3, 4, or 6 impair normal development of the cuticle and affect both basal and resistance protein-mediated defense against bacterial and fungal pathogens. Loss of ACBP3, 4, or 6 also inhibits the induction of systemic acquired resistance (SAR) due to the plants inability to generate SAR inducing signal(s). Together, these data show that ACBP3, ACBP4 and ACBP6 are required for cuticle development as well as defense against microbial pathogens.